Congenital Mesoblastic Nephroma at Birth: A Case Report and Detailed Analysis - Hina Yousuf; Aisha Bakhtiar (Journal of Liaquat National Hospital)
Renal tumours in infants and children, ranging from benign to highly malignant, present a significant medical challenge and constitute approximately 3% of all kidney tumours in neonates. This study focuses on congenital mesoblastic nephroma (CMN), the most common renal tumour in neonates. We present a case of a full-term neonate born with a palpable abdominal mass, diagnosed as the cellular subtype of CMN. Typically benign, CMN often appears as a symptomless abdominal mass without cystic elements. The neonate underwent a radical left nephroureterectomy, and a histopathological examination confirmed the diagnosis. Despite its generally benign nature, CMN can lead to serious complications, necessitating early surgical intervention. Our case, 18 months post-operation, shows no evidence of recurrence, underscoring the importance of regular surveillance in managing this rare renal tumour in neonates. This review discusses the diagnostic modalities, subtypes, genetic implications, and varying clinical outcomes associated with CMN, contributing to the understanding and management of this rare pediatric condition.